MEDIA KARTU HURUF DALAM UPAYA MENINGKATKAN KEMAMPUAN MENGENAL HURUF PADA ANAK USIA DINI - Veryawan Veryawan (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
In general, the objectives of improving learning to be achieved fromthis activity are: improving early childhood learning outcomes,improving early childhood language skills, improving children'sabilities in language activities, training children's thinking skillslogically and systematically and developing children's abilities inutilizing various media learning. This learning improvement is a typeof classroom action research that includes planning, action,observation, and reflection. The subjects of this study were 15students of RA As Salam in group B-I consisting of 5 boys and 10 girlswith the theme developed was the plant theme. The object of thisresearch is children's activities to find out how enthusiastic studentsare in recognizing letters through letter cards media. The resultsobtained in the ability to recognize letters have increased. Before theaction was taken, the level of the ability to recognize letters was stillvery low, after the first cycle class research was carried out it gained44% and in the second cycle it increased to 80%. After conductingresearch starting from pre-cycle, cycle I and cycle II, it was concludedthat the ability to recognize letters of the B-I RA As Salam groupchildren had increased through the use of letter cards media.